PENGEMBANGAN E-MODUL DENGAN CONSTRUCT-2 PADA PRAKTIKUM MICROSOFT OFFICE KELAS X MA DARUL HIKMAH - Muhammad Saifullah Fattah; Abdul Haris Indra Kusuma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of information technology in education has increased the need for interactive learning media that support students' independent learning. However, Microsoft Office practical learning in schools still relies heavily on conventional teaching materials, resulting in students being less actively engaged and experiencing difficulties in understanding the material independently. Therefore, more innovative learning media are needed. This study aims to develop a Construct 2-based E-Module for Microsoft Office practical learning for tenth-grade students at MA Darul Hikmah Tulungagung. The research employed the Research and Development (R&D) method using the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observations, interviews, and validation questionnaires involving material experts, media experts, and students as users. The validation results indicated that the E-Module achieved a score of 97.37% from the material experts, 97.5% from the media experts, and 99% from student responses, all of which were categorized as highly valid. Therefore, the Construct 2-based E-Module is considered suitable for use as an interactive learning medium to enhance students' understanding and independent learning in Microsoft Office practical lessons.